Economic integration among developing countries - Kahnert, F.; Richards, P.; Stoutjesdijk, E.; Thomopoulos, P. (Paris : Development Centre, Organisation for Economic Co-operation and Development, 1969)
This study attempts to place an assessment of the benefits and drawbacks of existing integration schemes in an overall economic context. In addition, it defines those areas in which foreign aid policy could help to improve the chances of economic integration among developing countries
Bibliography: p. 159-162.
osc 24/09/2018
Loans
Keywords: Economic integration; Developing countries